EFFORT TO PRODUCTION AND INCOME IMPROVEMENT OF PADDY FARMING ON DESA MANDIRI PANGAN PROGRAM (Study Case in Desa Ngunut Kecamatan Babadan Kabupaten Ponorogo) - dwinda rahmadya; S Syafrial; S Suhartini (Socio-Economics/Agribusiness Department, 2019)
This study aims to 1) Determine the production, production costs and income of farmers who follow the Food Independent Village Program and who do not follow in the Ngunut Village, Ponorogo Regency. 2) Analyze the factors that influence the production of rice farmers who follow and who do not follow the Mandiri Food Village Program in Ngunut Village, Ponorogo Regency. 3) Analyzing the allocative efficiency of the production of rice farmers who followed and who did not participate in the Food Independent Village Program in Ngunut Village, Ponorogo Regency. Data analysis method used to determine the factors that influence rice farming in Ngunut Village, Babadan Subdistrict is income analysis, multiple linear regression, and allocative efficiency analysis using SPSS application. The results showed that 1. Rice farmers who participated in the Desa Mandiri Pangan Program produced an average of 3 tons of rice while farmers who did not participate in the 1.5-ton Food Independent Village Program. Farmers who participated in the Mandiri Pangan Village Program spent production costs of Rp. 5,933,141, while for the income obtained was Rp. 8,850,772. Farmers who did not participate in the Mandiri Food Food Program spent production costs of Rp 5,623,610 while for the income obtained was Rp 1,496,703. Production factors for rice farming were in Ngunut Village, Babadan Subdistrict, namely seeds, petrochemical fertilizer, orgasm fertilizer, and Bio Prisma fertilizer.